Penerapan balance scorecard untuk menilai kinerja apotek dalam aspek keuangan dan proses internal : literature review - Surya Dharma, Berly; Mudia Puspa, Oti; Utama , Teguh; Sari , Seftika (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Increasingly fierce competition in the pharmaceutical sector requires pharmacies to maintain and continuously improve their performance to maintain customer satisfaction and trust. This study aims to assess pharmacy performance, focusing on two main perspectives: internal business processes and finance. The method used was a systematic review of journals using PRISMA guidelines, using data from Google Scholar for the period 2015–2025.Of the 200 articles found, seven met the inclusion criteria and were further analyzed. The study revealed that 43% of the journals reported challenges with medication availability and customer information, although service aspects such as dispensing times and medication labeling generally met standards. From a financial perspective, most pharmacies experienced a decline in key financial indicators such as Return on Investment (ROI), profit margin, and inventory turnover, indicating challenges in inventory management and profitability. Some pharmacies, such as PT Apotik Bangka Pratama, demonstrated good financial performance and internal processes with a score of 75% (category A), while others, such as Apotek Kasih Farma and Toko Obat Sejahtera Bali, faced significant financial performance declines. This study emphasized the importance of optimizing internal processes through the implementation of standard operating procedures (SOPs), human resource training, and service innovation, as well as the need for a more aggressive and efficient financial strategy. Management can take focused, evidence-based improvement measures to enhance service quality and pharmacy competitiveness